Refined lightweight inertial navigation system for micro air vehicle applications. Issue 2 (June 2017) - Hrishikeshavan, Vikram; Chopra, Inderjit
This paper discusses the design, hardware and software methodology, and testing of an ultralight inertial navigation system (Embedded Lightweight Kinematic Autopilot-Revised (ELKA-R)) that can be used as a controller in a wide range of micro air vehicle systems. ELKA-R was designed using the 32-bit low-power ARM Cortex-M4 microprocessor as the microcontroller unit. The microcontroller unit interfaced with state of the art 9 degrees-of-freedom inertial measurement unit using inter-integrated circuit communication (I 2 C) protocol. A wireless transceiver was also incorporated with serial peripheral interface to wirelessly coordinate pilot inputs and sensor information with a remote basestation. Multiple timer protocols were configured to generate individual driver signals to a wide variety of motor and actuator configurations. The printed circuit board was designed as a four layer layout. ELKA-R weighed 1.7 g with a board area of 4.82 cm 2, thus making it one of the smallest and lightest kinematic autopilots in open literature that can be applied to any generic micro air vehicle system. ELKA-R was tested on a variety of micro air vehicle flight demonstrators. Hover stabilization rates of 1000 Hz were achieved which were comparable to the autopilots on larger quad rotor systems such as DJI Phantom and AR-Drone. Oscillations in attitude were reduced by up to 50%–70% when compared with a previous generation lightweight autopilot.